Upscaling Aboveground Biomass Estimation at Low-land Royal Belum Forest Reserve Using Unmanned Aerial Vehicle Image - Rasib, Abd Wahid; Mohd Ali, Hamzah; Alvin, L.M.S.; Kanniah, K.D.; Idris, Nurul Hawani; Omar, Hamdan; Faidi, Azahari; Dollah, Rozilawati; Anjang Ahmad, Mustaffa (International Journal of Integrated Engineering, 2018)
Lowland  tropical  rainforests have the largest  aboveground  biomass compared to other types of tropical  rainforest. Furthermore, lowland tropical rainforests have a high density of trees and various types of vegetation  species. Due to the limitation  in  measurement  method  that occurs  in  lowland  tropical  rainforest, the information  regarding  aboveground  biomass  is  very limited to small-scaled  area  compared with the existing  method  based  on  experimental  plot tree census. Hence, this  study  suggested  the upscaling method that enables the estimation of biomass for a larger area using a small size experimental plot. This study is conducted  at  Sungai  Papan  Royal  Belum  Forest Reserve, Perak with  an  area approximate  to  22  hectares  and based on  the experimental plot of 100 × 100 m. Eight vegetation indices obtained  from UAV multispectral  images  and  field data  are  used  to  determine the best upscaling equation. This study successfully determined that TAGB VS SR gives the highest correlation with = 0.7224, RMSE= 1.1700 and t-test= 15.647/100. The final output  of  this research  study  shows  the  upscaling  map of  aboveground  biomass  concentration  at  Sungai Papan, Royal Belum Forest Reserve